Advanced organic-inorganic hybrid fillers as functional additives for poly(vinyl chloride) - Tomaszewska, J.; Klapiszewski, Ł.; Skórczewska, K.; Szalaty, T. J.; Jesionowski, T. (Polimery, 2021)
Functional hybrid fillers (kraft lignin conjugated with Sylobloc® 41 silica) were obtained using a process of mechanical grinding of precursors. The products underwent comprehensive physicochemical and dispersive-morphological analysis. The organic-inorganic fillers have good homogeneity and a relatively high surface area. Composites of rigid poly(vinyl chloride) as a matrix with these specific dual fillers were produced in molten state. Data on the processing properties of the blends show the beneficial impact of fillers on gelation time. The presence of lignin/silica fillers strongly influences the thermal stability of PVC as well as Vicat softening temperature.